2022
DOI: 10.3390/admsci12010033
|View full text |Cite
|
Sign up to set email alerts
|

Seven Steps to Strategic SDG Sensemaking for Cities

Abstract: This practitioner paper is based on the need to make sense of UN Agenda 2030 and Sustainable Development Goals (SDGs) at the city level and in an urban context. We examine the need to explain how to utilise the SDGs in strategic, tactical and operative urban development. We find that there are knowledge and practise gaps in how to localise SDGs in the urban context. This need and the lack of existing tools has led to the development of a strategic sensemaking process, which has been tested and developed with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…The starting point in our research was the Sustainable Development Report 2022, from the analysis of which we observed a series of paradoxes both between the results of the SDG Index and between the results presented in this report and those presented by other researchers (i.e., Horan, 2020;Puertas and Bermúdez, 2020;Wang et al, 2020;Rocchi et al, 2022;Taajamaa et al, 2022).…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…The starting point in our research was the Sustainable Development Report 2022, from the analysis of which we observed a series of paradoxes both between the results of the SDG Index and between the results presented in this report and those presented by other researchers (i.e., Horan, 2020;Puertas and Bermúdez, 2020;Wang et al, 2020;Rocchi et al, 2022;Taajamaa et al, 2022).…”
Section: Introductionmentioning
confidence: 77%
“…Our methodology consists of a critical analysis of literature starting from the Sustainable Development Report 2022, the 2030 Agenda for Sustainable Development, and the representative work of relevant scholars (i.e., Hwang and Yoon, 1981;Bravo, 2014;Costanza et al, 2016;Dhaoui, 2018;Ding et al, 2018;Burlea-Schiopoiu, 2019;Horan, 2020;Puertas and Bermúdez, 2020;Wang et al, 2020;Rocchi et al, 2022;Sachs et al, 2022;Taajamaa et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Through the VLR, the city strove to incorporate the SDGs into key municipal processes such as budgeting or public relations. As such, Espoo sought to realise policy integration by bringing together the initiatives of its three largest departments (education and culture, health, and infrastructure), while helping internal capacity building and creating the conditions for better integration across policies in the future 45 so that 'everyone [in the organisation] can understand what their work means in relation to the [SDGs] targets and indicators' (I5). Moreover, the city aimed at maximising engagement with citizens by working with students in middle and high schools, asking them what they considered the most relevant projects for the city-an activity that resulted in the selection of around 90 projects to be included in the VLR.…”
Section: The Design Of the Vlr Processmentioning
confidence: 99%
“…Resilience also cuts across the UN Agenda 2030 (Croese et al, 2020). Countries worldwide have placed the UN 2030 Agenda and, in particular, the Sustainable Development Goals (SDGs) at the center of the sustainable policies needed to achieve sustainability targets, mitigate climate change, and improve city resilience (Niemets et al, 2021;Taajamaa et al, 2022;Tarsitano et al, 2019).…”
Section: Introductionmentioning
confidence: 99%